ÙØ¹Ø§Ù„ÙŠØ© ÙˆØ³Ø§Ø¦Ù„ Ø§Ù„ØºØ§Ø² Ù„ØªØ±Ù‚ÙŠØ© Ø¥ØªÙ‚Ø§Ù† Ø§Ù„Ù…ÙØ±Ø¯Ø§Øª Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙÙŠ Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ù…ØªÙˆØ³Ø·Ø© Ù†Ù‡Ø¶Ø© Ø§Ù„ÙˆØ·Ù† - Siti Muliani; Nurul Aini; Idiatussaufiah Idiatussaufiah (Lughatu Ad-Dhat, 2022)
This research aims to test the effectiveness of the gas media method in improving the mastery of Arabic vocabulary for the seventh grade in the school of recitation, bearing in mind that this method is interesting to increase students' enthusiasm and add its own challenges. This research uses quantitative research. The type of research used is an experimental research by dividing two classes into two groups, the experimental group and the control group that were chosen randomly. The control group, then search for the effect of the quantitative treatment through the post-test of the two groups. The researcher collects the data and then simplifies all the collected data, presenting them in an orderly order. Which is then calculated using the SPSS application. This research was applied to a sample of 53 students in the school of recitation. The mean value of the pretest results performed in the control group was 58.85 out of the highest score of 70 while the lowest score was 30. Meanwhile, the post-test score was with a mean score of 79.00 out of the highest score of 97 and the lowest score of 60. The results showed that after performing the pre- and post-test, the results of the independent sample t-test for the experimental group were obtained with a t-count of 563 > 1.675. H0 is rejected, Ha is accepted, and it can be concluded that puzzle modes can improve the mastery of Arabic vocabulary.